2013
DOI: 10.1111/1574-6968.12314
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction of the stress response factors ChAP1 and Skn7 in the maize pathogenCochliobolus heterostrophus

Abstract: The transcription factors ChAP1 and Skn7 of the maize pathogen Cochliobolus heterostrophus are orthologs of Yap1 and Skn7 in yeast, where they are predicted to work together in a complex. Previous work showed that in C. heterostrophus, as in yeast, ChAP1 accumulates in the nucleus in response to reactive oxygen species (ROS). The expression of genes whose products counteract oxidative stress depends on ChAP1, as shown by impaired ability of a Δchap1 mutant to induce these 'antioxidant' genes. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…We found that multiple TFs ( FgAP1 , FgSKN7 , GzZC086 , GzZC236 , GzHOME001 and GzC2H010 ) co‐regulated the expression of FCA7 in response to oxidative stress, reflecting a complex network of transcriptional activators of antioxidant genes. A cooperative role of these TFs has been reported in previous studies (Calvo et al ., ; Mulford and Fassler, ; Shalaby et al ., ). In S. cerevisiae and C. heterostrophus , Yap1 and Skn7 cooperate to activate the expression of antioxidant genes in response to oxidative stress (Mulford and Fassler, ; Shalaby et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that multiple TFs ( FgAP1 , FgSKN7 , GzZC086 , GzZC236 , GzHOME001 and GzC2H010 ) co‐regulated the expression of FCA7 in response to oxidative stress, reflecting a complex network of transcriptional activators of antioxidant genes. A cooperative role of these TFs has been reported in previous studies (Calvo et al ., ; Mulford and Fassler, ; Shalaby et al ., ). In S. cerevisiae and C. heterostrophus , Yap1 and Skn7 cooperate to activate the expression of antioxidant genes in response to oxidative stress (Mulford and Fassler, ; Shalaby et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A cooperative role of these TFs has been reported in previous studies (Calvo et al ., ; Mulford and Fassler, ; Shalaby et al ., ). In S. cerevisiae and C. heterostrophus , Yap1 and Skn7 cooperate to activate the expression of antioxidant genes in response to oxidative stress (Mulford and Fassler, ; Shalaby et al ., ). In F. graminearum , the genetic relationship between orthologues of Skn7 and Atf1 has been investigated (Jiang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Because it has been shown in some fungi that genes that are regulated by Skn7 are also regulated by Ap1 (19,21,36,59), the regulatory function of both proteins was analyzed in B. cinerea. To gain a first impression, a set of OSR genes was selected for expression analyses via Northern blotting (thioredoxin reductase, trr1…”
Section: Bcskn7 Is Involved In Mycelium-derived Host Infection Via Inmentioning
confidence: 99%
“…The most important research progress on C. heterostrophus focuses on genome sequencing of races T and O Turgeon & Baker, 2007) and determination of essential genes required for synthesizing T-toxin in race T (Baker et al, 2006;Inderbitzin, Asvarak, & Turgeon, 2010). Many transcription factors are involved in stress response, toxin production or virulence regulation (Lev et al, 2005;Ronen, Shalaby, & Horwitz, 2013;Shalaby, Larkov, Lamdan, & Horwitz, 2013;Zhang et al, 2013;Bi, Wu, Zhu, & Gillian Turgeon, 2013;Ganem et al, 2004;Horwitz et al, 1999;Igbaria et al, 2008;Izumitsu et al, 2009;Lev, Sharon, Hadar, Ma, & Horwitz, 1999;Oide et al, 2010;Wu, Oide, Zhang, Choi, & Turgeon, 2012). Among race types, race O is the predominant agent of maize disease in China; maize resistance against race O is determined by quantitative trait locus (Balint-Kurti et al, 2007;Carson, Stuber, & Senior, 2004).…”
Section: Introductionmentioning
confidence: 99%